Los procesos de topicalizacián en latin: algunas consideraciones preliminares - Gutiérrez, Marca A. (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
A scrupulous analysis of the words which can work as themes reveals that this grammatical function is in fact a very complex one. To face such a challenge we have used theoretical premises taken from the Gestalt theory and adapted to linguistics. It is particulary important, from this point of view, not only hearer’s perception of the message, but also final speaker’s intention. Last, but not least, themes are sometimes only virtual linguistic units which do no exist apart from context.